Nafkah Sebagai Konsekuensi Logis Pernikahan - Darmawan Darmawan (AL-HUKAMA, 2020)
This research aims to find out what are the forms of zahir (material) and inner (non-material) livelihood that a husband must give to his wife? Is the living provided by the husband because of the obedience of the wife or because of the marriage contract? By using a qualitative approach. Zahir livelihoods are related to basic daily necessities, which can be classified as الكسوة (clothing), الطعام (food) and السكن (board), household costs and maintenance, the cost of children's education. While the inner livelihood can be classified as: 1) Husband teaches the values of tauhid, morality and worship. 2) Husband treats wife well, gently. 3) Husband gives sovereignty to wife to interact with society. 4) The husband gives an explanation of what the wife is lacking. 5) Having an intimate relationship between husband and wife. Livelihood is the logical consequence of the marriage contract, both zahir and inner. Zahir is a gift from the husband that must be given to the wife when the marriage contract is completed, provided that they both exercise their rights and obligations. If a wife does not fulfill her obligations as a wife, then the husband is not obliged to provide zahir support to his wife. Meanwhile, the inner livelihood is the living that the husband must give to the wife from the completion of the marriage contract until the end of the marriage, whether the wife is obedient or not.